Department of Maintenance in the Army Hospital: An Overview - Karki, Ram Nahadur (Medical Journal of Shree Birendra Hospital, 2010)
DOI:  10.3126/mjsbh.v9i1.3490Medical Journal of Shree Birendra Hospital Vol.9(1) 2010 36-39